1962
DOI: 10.1084/jem.115.3.475
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Tubercle Bacillus-Histiocyte Relationship

Abstract: Studies of passive transfer of cellular resistance, as manifested by refractoriness to necrotization with virulent tubercle bacilli, have shown that immune histiocytes or immune lymphocytes were effective transferring agents; immune polymorphonuclear leucocytes and immune serum as well as comparable cells from normal animals lacked this capacity. Comparisons of immune histiocytes and immune lymphocytes showed that the former cells were more efficient; this was indicated by (a) the smaller number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1964
1964
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Recent reports on the passive transfer of acquired resistance in tuberculosis (7,8,11,12,34,36) can also be recognized as presentations of the cellular nature of immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports on the passive transfer of acquired resistance in tuberculosis (7,8,11,12,34,36) can also be recognized as presentations of the cellular nature of immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed descriptions of procedures and materials used in these studies have been described in earlier reports (1)(2)(3)(4)(5)(6) and are therefore briefly described herein.…”
Section: Methodsmentioning
confidence: 99%
“…Details concerning the test for cellular resistance have been previously described (4). Briefly, the procedure was as follows: part of the histiocytes which had been collected from donor animals or recipient animals was sedimented by centrifugation and redispersed in a small volume of 0.25 per cent trypsin in Tyrode's solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established by many investigators that acquired resistance against a facultative intracellular parasite,Mycobacterium tuberculosis, depends upon cell-mediated immunity [11,14,18,25]. Experimental findings during the last decade have shown that the effector cells of this type of cellmediated immunity are immune macrophages [1,2,17,29].…”
mentioning
confidence: 99%